The effect of teaching with the SWOM strategy health awareness for students Faculty of Basic Education (Journal of the College of Basic Education, 2022)
The present study aims at identify The Influence of Teaching by SWOM Strategy on Awareness Health Matter the Students College of Basic Education and due to following null hypotheses have been formulated by the researcher:-There is no significant difference at (0,05) level between the mean scores of the experimental group students who are taught according to the SWOM and the mean scores of the control group students who are taught according to the conventional method in the accordance with the scheme of the health education subject-matter.To achieve the validity of those null hypotheses, the researcher an experiment lasted for one complete semester, the experimental design for posttest two equivalent groups (the experimental and control groups) and the instrument of the experiment was a posttest of the scheme of the health awareness and each goanna adjust the other partially. The experiment has been conducted on the student of second grade of the Department of Sciences in the College of Basic Education , Al-Mustansiriyah University, the department has been selected deliberately among other ones which includes the branches (Biology, Chemistry and Physics). The Biology's has been selected to be the experimental group which based upon using SWOM as teaching strategy with a sample consists of (32) male and female students while the Chemistry's has been selected to be the control group which based upon using the conventional method as teaching technique with a sample (28) male and female students .The two groups have been equalized with variables of (pre-knowledge, intelligence and health awareness) As well as adjustment of other extraneous variables for the safety of the experiment .To achieve the validity of the null hypothesis, the health awareness scale constructed (al-ubaidi, 2013), of 40 items is adopted. By using t-test as an instrument of independent non-equivalent samples, the researcher has come out with the following results: Superiority of the experimental group participants who are taught according to the SWOM and those of the control group who are taught according to the conventional method in accordance with scheme of the health education subject-matter. Finally, in the light of findings the researcher has drawn many conclusions and put forward and a number of recommendations and suggestions for further studies.